Influence of stage-specific and location-related intratumoral microbiota on prognosis and metabolic reprogramming in non-small cell lung cancer - Zhao, Yuwei; Tong, Zhuang; Liu, Lin; Yang, Rongjie; Chen, Zhongfeng; Wang, Zheng (Frontiers in Immunology, 2026)
IntroductionMounting evidence links intratumoral microbiota to tumor progression and immune regulation, but stage-specific and location-related microbial characteristics in NSCLC remain insufficiently explored.MethodsTumor and adjacent non-tumor tissues from 21 NSCLC patients were analyzed using 16S rRNA gene sequencing to profile the intratumoral microbiota. Functional pathway analysis, in vitro co-culture experiments (A549/HCC827 cells), and in vivo mouse models were employed to validate microbial functions.ResultsMicrobial composition exhibited significant heterogeneity by tumor stage (early vs. advanced) and anatomical location (upper vs. lower lobes). Bacteroides was identified as a key genus enriched in early-stage tumors and correlated with improved prognosis. Functional analysis revealed enrichment of tumor-associated microbiota in metabolic and biosynthetic pathways (e.g., carbon metabolism, amino acid biosynthesis). Further experiments demonstrated that Bacteroides significantly suppressed NSCLC cell proliferation, inhibited migration, and promoted apoptosis, with anti-tumor effects mediated by remodeling the tumor immune microenvironment.DiscussionThese findings elucidate intricate associations between intratumoral microbiota, immune cell infiltration, and patient prognosis, highlighting Bacteroides as a potential prognostic biomarker and therapeutic target for NSCLC